Selective Loss of Smaller Spines in Schizophrenia - MacDonald, Matthew L. (Am J Psychiatry, 2017)
OBJECTIVE: Deceased density of dendritic spines in adult schizophrenia subjects has been hypothesized to result from increased pruning of excess synapses in adolescence. In vivo imaging studies have confirmed that synaptic pruning is largely driven by the loss of large/mature synapses. Thus, increased pruning throughout adolescence would likely result in a deficit of large spines in adulthood. Here, we examined the density and volume of dendritic spines in deep layer 3 auditory cortex of 20 schizophrenia and matched control subjects as well as aberrant voltage-gated calcium channel subunit protein expression linked to spine loss. METHODS: Primary auditory cortex deep layer 3 spine density and volume was assessed in 20 pairs of schizophrenia and matched comparison subjects in an initial and replication cohort (12 and 8 pairs) by immunohistochemistry-confocal microscopy. Targeted Mass Spectrometry was used to quantify postsynaptic density and voltage-gated calcium channel protein expression. The effect of increased voltage-gated calcium channel subunit protein expression on spine density and volume was assessed in primary rat neuronal culture. FINDINGS: Only the smallest spines are lost in deep layer 3 primary auditory cortex of schizophrenia, while larger spines are retained. Levels of the tryptic peptide ALFDFLK, found in the schizophrenia risk gene CACNB4, inversely correlated with the density of smaller, but not larger, spines in schizophrenia subjects. Consistent with this observation, CACNB4 overexpression resulted in a lower density of smaller spines in primary neuronal cultures. CONCLUSION: These findings require a rethinking of the over pruning hypothesis, demonstrate a link between small spine loss and a schizophrenia risk gene, and should spur more in-depth investigations of the mechanisms that govern new/small spine generation and stabilization under normal conditions as well as how this process is impaired in schizophrenia.